Feasibility of membrane ultrafiltration as a single-step clarification and fractionation of microalgal protein hydrolysates - Soto-Sierra, Laura; Nikolov, Zivko L. (Frontiers in Bioengineering and Biotechnology, 2022)
Protein hydrolysates are one of the most valuable products that can be obtained from de-lipidated microalgae. The advantages of protein hydrolysates over other protein products encompass enhanced solubility, digestibility and potential bioactivity. The development of an economically feasible process to produce protein hydrolysates should rely on maximizing the release (isolation) of hydrolyzed native protein from the de-lipidized biomass and subsequent fractionation of hydrolyzed protein slurry. Previously, we reported a process consisting of direct hydrolysis of delipidated biomass and fractionation of algal slurry (which consisted of) by acidic precipitation of cell debris and unhydrolyzed protein, precipitate wash, centrifugation, and depth filtration. In this study, this process to one involving tangential flow ultrafiltration as a single step alternative to centrifugation, precipitate wash, and depth filtration steps. The results demonstrate that tangential flow ultrafiltration process was superior to the traditional protein fractionation method in several ways. First, the membrane diafiltration process uses a single and easily scalable unit operation (tangential flow filtration) to separate and “wash out” hydrolyzed protein from the algal residue. Second, the protein recovery yield achieved with the tangential flow process was >70 % compared to 64% previously achieved by centrifugation and depth filtration method. Finally, membrane filtration-processed protein hydrolysates were more heat and pH stable than the alternative process.